A facile strategy for fabricating self-healable, adhesive and highly sensitive flexible ionogel-based sensors. Issue 45 (11th November 2022) - Wu, Yingxue; Jiang, Wenxing; Zhao, Tianyu; Wang, Jiadong; Zhang, Xianhong; Chen, Dong; Ma, Yuhong; Yang, Wantai
Abstract : An adhesive, self-healable and transparent ionogel-based strain and temperature sensor with high sensitivity (gauge factor up to 6) and a wide sensing range was fabricated based on a green deep eutectic solvent. Abstract : Stretchable ionogels have been intensively investigated for the development of flexible and wearable sensors. Integration of excellent mechanical properties, high conductivity, reliable adhesiveness, remarkable self-healing ability, favorable transparency and biocompatibility is highly desired for ionogel-based flexible sensors but is still challenging. Herein, a high-performance flexible sensor based on a well-designed ionogel with excellent comprehensive properties was facilely fabricated via introducing oppositely charged poly(acrylic acid) (PAA) and polyethyleneimine (PEI) into a green deep eutectic solvent (DES) composed of biocompatible choline chloride and urea. Dynamic physically cross-linked networks were efficiently constructed through noncovalent interactions, including PAA/PEI electrostatic interactions and hydrogen bonding interactions between PAA/PEI and DES. The as-prepared PAA/PEI/DES ionogels exhibit well-tailored mechanical properties, high conductivity, desirable transparency, strong adhesiveness and highly efficient self-healing ability simultaneously. More importantly, the assembled ionogel-based sensor possesses excellent sensory capabilities towards strain and temperature, including high sensitivity (gauge factor up to 6), wide sensing range (1–600% strain), short response time and outstanding durability. The fractured sensor could be easily healed at 40 °C and their initial sensing performance can be fully restored. This study offers a promising strategy for fabricating biocompatible, flexible and highly sensitive ionogel-based wearable sensors for a full-range of human motion detection.